The Anthelmintics Activity of Ethanol Extract of African Leaf (Vernonia amygdalina) on Mortality of Fasciola gigantica in Vitro - Dhio Asmaydo; Iwan Sahrial Hamid; Kusnoto Kusnoto; Mohammad Sukmanadi; Endang Suprihati (Universitas Airlangga, 2019)
The Aims of this study is to know the anthelmintics activity of ethanol extract of african leaf (Vernonia amygdalina) on mortality of Fasciola gigantica in Vitro. Method that used in the research was a completely randomized design. There were five treatments and each treatment was done in four replications. This research used ten Fasciola gigantica in each treatment for all replications. The observation and recording of dead Fasciola gigantica was done at 2, 4, 6, 8, and 10 hours.Â Fasciola gigantica were declared dead if there was no movement when disturbed by anatomy tweezers and when dipped in slightly warm water (500C). The obtained data was analyzed using ANOVA and continued with Duncan Multiple Range Test. The result of this research show that ethanol of extract of African Leaf (Vernonia amygdalina) has activity anthelmintic on mortality of Fasciola gigantica in Vitro. Ethanol extract african leaf (Vernonia amygdalina) with concentration of 1.4% is the optimal concentration of anthelmintics. This higher the concentration of the extract, the higher the property of anthelmintics.